Patient motivation: A concept analysis - Patcharin Khomkham; Pootsanee Kaewmanee (Belitung Raya Foundation, 2024)
Background:  Patient motivation is crucial in maintaining health-improving activities and helping patients recover from illnesses. Despite extensive research on patient motivation, this concept has not been clearly defined and remains ambiguous. The latest analysis of patient motivation was over two decades ago, thus necessitating the need to reexamine it in more updated literature. Objective: This study aims to explore the concept of patient motivation. Methods: The eight-step approach of Walker and Avant was used: concept selection, determining analysis aim, identifying concept use, defining attributes, model case identification, borderline and contrary case identification, antecedents and consequences identification, and empirical referent identification. Five databases, CINAHL, Cochrane, Medline, PubMed, ProQuest, and ScienceDirect, were searched for published works between 2014 and 2024 using the keywords "patient" and "motivation." Results: The identified attributes of patient motivation are a psychological drive, a desire to adopt healthy behaviors, and goal-directed action. Antecedents of patient motivation are self-efficacy, provider-patient communication, and social support. Patient motivation leads to consequences, including healthier lifestyles and greater adherence and compliance. Conclusion: The present concept analysis draws upon current literature to suggest the antecedents, attributes, and consequences of patient motivation. Nurses can promote healthier lifestyles and greater adherence and compliance among patients by employing techniques to raise self-efficacy and provide social support while enhancing patient-centered interactions.